Facies Analysis and Sequence Stratigraphy of the Barremian Succession in the Majnoon oil field, Southern Iraq. (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
The Barremian succession in the present study is represented by the Zubair Formation which the most significant sandstone reservoir in Iraq. The area of study is located in the Southern part of Iraq at the Majnoon oil fields, within the Mesopotamian basin.The petrographic study showed that quartz mineral is the main component of the sandstone in Zubair Formation with minor percentage of feldspar and rare rock fragments to classified as quartz arenite. There are five lithologic changes (lithofacies) that have characterized the studied succession: - course to medium sandstone well sorted, fine sandstone well sorted, course to medium sand poorly sorted, clayey sandstone poorly sorted, and shale.  These lithofacieses were deposited in the deltaic environments as three associated facies [delta plane, delta front and lacustrine(marsh)].The different lithofacies contributed to division of the Zubair Formation into three distinct rock units, which had been used in interpreting and distributing the suggested environments. The lower unit is composed of shale with lenses of fine sand with high organic matter, and it was deposited in the flood-delta plain environment. The presence of the delta plain associated facies overlaying the unconformity surface (SB1) refer to the transgressive system tract (TST). This stage finished with appeared the channel fill deposit to mark a high-stand system tract (HST).The middle unit is composed of sandstone with the shale inter layers with high amount of heavy minerals, which was deposited in the distributary-mouth-bar within the delta front environment. There are two sequences as TST in this part which end with the maximum sea level rise (mfs) to mark the upper part of the Zubair Formation.While the upper part is composed of shale with high amount of pyrite and organic matters. This represents the lacustrine (marsh) associated facies within the delta plain environment which deposited during the high stand stage. The sea level rise was marked the end of this stage when deposition the upper part of Zubair Formation, and the beginning of deposition the Shuaiba Formation as shallow carbonate marine.